Comparative assessment of the U.S. State of Florida's Marine Life regulations for its commercial marine aquarium fish fishery. (March 2023) - Anderson, Paul A.; Pomeroy, Robert S.
Abstract: Governments in select locales around the world have recently either restricted or closed commercial marine aquarium fisheries, impacting the livelihoods of fishers, traders, and others who depend on them. This paper offers an objective assessment of Florida's commercial marine aquarium fish fishery and its regulatory landscape to inform and guide stakeholders about management strategies for the fishery moving forward, and to highlight successful regulations in place in Florida that merit consideration for adoption in other source locales around the world. The study discovered that the State has a strong regulatory structure for the commercial fishery operated by the Florida Fish and Wildlife Conservation Commission; practicing co-management with fishers, and utilizing license and permitting requirements, conventional fisheries management measures and technical actions to regulate fishing mortality, and rights-based management approaches. Additionally, both fisheries-independent and dependent surveys have been conducted in recent years to assess the fishery. Consequently, the vast majority of fish species collected commercially for the trade indicate stable or increasing catch trends in Florida waters over 10 + years. Moving forward, the fishery can benefit from an assessment of the economic impacts of the regulatory framework on its fishers, a statewide fisheries management plan specific for the fishery, the further development of a comprehensive program for fisheries data collection and analysis to address data gaps, an assessment of resources at hand and those needed to implement these recommendations, and the elevation of marine aquarium fisheries for support at the national level to support state-level management. Highlights: Florida's Marine Life regulations are comparatively comprehensive. Catch trends for most Florida marine aquarium fish species are stable or increasing. Economic impact analysis and routine fisheries trends analyses are recommended. Identify resource needs to garner state and federal support for management actions. Marine aquarium fisheries management plans are recommended.